Hyaluronan: molecular size‐dependent signaling and biological functions in inflammation and cancer. (21st February 2019) - Tavianatou, Anastasia G.; Caon, Ilaria; Franchi, Marco; Piperigkou, Zoi; Galesso, Devis; Karamanos, Nikos K.
Abstract : Hyaluronan (HA) is a linear nonsulfated glycosaminoglycan of the extracellular matrix that plays a pivotal role in a variety of biological processes. High‐molecular weight HA exhibits different biological properties than oligomers and low‐molecular weight HA. Depending on their molecular size, HA fragments can influence cellular behavior in a different mode of action. This phenomenon is attributed to the different manner of interaction with the HA receptors, especially CD44 and RHAMM. Both receptors can trigger signaling cascades that regulate cell functional properties, such as proliferation migration, angiogenesis, and wound healing. HA fragments are able to enhance or attenuate the HA receptor‐mediated signaling pathways, as they compete with the endogenous HA for binding to the receptors. The modulation of these pathways could be crucial for the development of pathological conditions, such as inflammation and cancer. The primary goal of this review is to critically present the importance of HA molecular size on cellular signaling, functional cell properties, and morphology in normal and pathological conditions, including inflammation and cancer. A deeper understanding of these mechanisms could contribute to the development of novel therapeutic strategies. Abstract : Hyaluronan plays a crucial role in a plethora of biological processes. Hyaluronan fragments trigger various responses depending on their molecular size. This phenomenon occurs due to the different modes of interaction with the hyaluronan receptors. The hyaluronan receptor‐mediated signaling pathways regulate cellular behavior. Here, we discuss the hyaluronan molecular size effects in normal and pathological conditions, including inflammation and cancer.